Analysis of machining process and thermal conditions during vibration-assisted cortical bone drilling based on generated bone chip morphologies. (September 2020) - Bai, Xiaofan; Hou, Shujun; Li, Kai; Qu, Yunxia; Zhu, Weidong
Highlights: This paper analyses the results of temperature experiments and the different morphologies of bone chips to explore the different machining processes and thermal conditions in conventional and vibration-assisted drilling methods. Bone chips generated in the three drilling methods under the same drilling parameters were compared quantitatively by their morphology and granularity distribution. The favourable thermal condition in LFVAD is caused by its unique geometric chip breaking mechanism and cutting/separation motion, which can be verified by its fan-shaped chips. The dust-like chips from UVAD directly revealed substantial differences in this machining process compared to the other processes and illustrated the additional heat sources associated with this method. Abstract: When the temperature during bone drilling exceeds the safety threshold, the bone tissue surrounding the drilling site can be irreversibly damaged. To investigate the influence of vibration-assisted drilling (VAD) methods on the temperature increase during bone drilling and the causes for temperature increase, drilling experiments were performed on fresh bovine femur samples. The morphology and granularity distribution of the generated bone chips were innovatively used to directly compare the machining processes and thermal conditions of conventional drilling (CD), low-frequency vibration-assisted drilling (LFVAD), and ultrasonic vibration-assisted drilling (UVAD). The experimental results indicated that LFVAD produced the lowest temperature increase of 31.4°C, whereas UVAD produced the highest temperature increase of 44.1°C with the same drilling parameters. Additionally, the morphologies and granularity distributions of the bone chips significantly differed among these methods. We concluded that the smaller temperature increase in LFVAD was mainly attributed to the improved thermal conditions resulting from the periodic cutting/separation motion and the reliable geometric chip-breaking mechanism. In contrast, the unfavourable thermal conditions of UVAD were caused by the higher applied frequency, which created a significantly larger amount of friction heat. This was the main cause for the highest observed temperature increase, resulting in bone crushing processes that generated additional heat.